Skin Biopsy Diagnosis and Treatment - Fernando, Suran L. (IntechOpen, 2013)
Skin Biopsy - Diagnosis and Treatment is a collection of six chapters that includes an initial chapter on the site selection of a skin biopsy that optimizes diagnosis of various dermatological diseases and in many instances it is a therapeutic intervention and is useful in monitoring the response to therapy. The following five chapters encompass the application and role of skin biopsy to the overall diagnosis of certain conditions such as non-scarring and scarring alopecia, Langerhan cell neoplasms, severe cutaneous adverse reactions, pemphigus vulgaris and foliaceus, and oral lichen planus. An accurate diagnosis allows for an up to date discussion on the treatment of these complex conditions as the pathogenesis and the histologic findings are evolving and the therapeutic options are concomitantly emerging.